Analyzing genetic response mechanisms associated with copper homeostasis in Populus trichocarpa using a bioinformatics approach - Patterson, Eric, author; Pilon, Marinus, advisor; Bedinger, Patricia, committee member; Jahn, Courtney, committee member; Walters, Christina, committee member (Colorado State University. Libraries, 2013)
Copper is an essential micronutrient for plants and plays an important role in photosynthesis, respiration, hormone signaling, cell wall structure and wound healing. Copper deficiency can cause chlorosis, leaf curling, and weakened stems. It is proposed that under copper deficient conditions plants down regulate genes whose proteins use copper as a cofactor but also play an "unessential" role for the plants survival, thereby preserving copper for more "essential" proteins like plastocyanin or cytochrome-C oxidase. Down-regulation of "unessential" genes is performed by the copper microRNAs miR307, miR398, and miR408. This thesis increases our understanding of copper homeostasis in plants by analyzing the transcriptomic response of Populus trichocarpa to copper deficiency in four vegetative organs and applies this knowledge to the study of multi-copper oxidases. Organs have drastically different responses to copper deficiency with few genes being systemically differentially expressed and most genes that are differential expressed only are in one organ. Our data also show that not all genes are regulated to the same extent. Genes that are already highly expressed (>50 RPKM) under copper-sufficient conditions are only up-regulated 1- to 4-fold, while low expressed genes can be up-regulated as much as 8-fold. We go on to describe 25 unannotated genes as laccases based on their sequence similarity with known laccases from Arabidopsis and Populus. The laccases break up into seven phylogenetically distinct groups. Each of the seven groups have a distinct expression pattern across the four organs in response to copper deficiency that seems to be mediated by Cu-miRNAs miR397 and miR408.